Short-Circuit Switches Fault Analysis of Voltage Source Inverter using Spectrogram - Abdullah, Abdul Rahim; ahmad, nur sumayyah; Bahari, Norhazilina; Manap, Mustafa; JOPRI, MOHD HATTA (2013)
The identification of faults in voltage source inverter is highly required to ensure the reliability of the inverter. Early detection of the faults can greatly assist in maintenance of the system by avoiding possibly harmful damage borne out. This paper presents the analysis of short-circuit switches fault of voltage source inverter (VSI) using time frequency distribution (TFD). The TFD which is spectrogram represents current signal of the VSI in time-frequency representation (TFR) that provides temporal and spectral information of the signal. From the TFR, parameters of the signal are estimated such as average current, root mean square (RMS), total harmonic distortion (THD), total waveform distortion (TWD) and total non-harmonic distortion (TnHD). The results shows that the analysis using spectrogram gives information of the current signal of the VSI to identify shortcircuit switches